Factors Related to Treatment Outcomes in Low-risk Gestational Neoplasia. Issue 2 (March 2017) - Turkmen, Osman; Basaran, Derman; Karalok, Alper; Kimyon, Gunsu Comert; Tasci, Tolga; Ureyen, Isin; Tulunay, Gokhan; Turan, Taner
Objective: To define the factors associated with methotrexate (MTX) resistance in patients with low-risk gestational trophoblastic neoplasia (GTN). Methods: A total of 63 patients with low-risk GTN according to International Federation of Gynecology and Obstetrics (FIGO) criteria were included. A total of 37 (58.7%) patients were treated with successive doses of 1 mg/kg intramuscular (IM) MTX on days 1, 3, 5, and 7, and 0.1 mg/kg IM folinic acid (FA) on days 2, 4, 6, and 8, until β-human chorionic gonadotropin (hCG) levels were normalized. After the β-hCG value dropped to the normal level, an additional cycle of MTX/FA was administered. This protocol is defined as the standard protocol. In a watchful waiting protocol, the same 8-day IM MTX/FA regimen was given only once (n = 8) or twice (n = 18) to 26 (41.3%) patients and patients in whom β-hCG values declined were subjected to follow-up and no additional cycles were administered as long as there was a decrease in β-hCG value. Clinical response and factors affecting therapeutic outcomes were analyzed retrospectively. Results: Of 63 patients, 47 (74.3%) were cured with primary MTX/FA treatment irrespective of any protocol. Of the 16 patients who were not able to be treated with primary MTX/FA, 3 were treated with single-agent actinomycin-D and 11 were treated with multi-agent chemotherapy. Univariate analysis showed that a pretreatment β-hCG level of ≥5000 IU/L was related to reduced therapeutic response (p = 0.001). The FIGO score, antecedent gestational pathology, and treatment with standard or watchful waiting protocol were not related to treatment response. Conclusions: The level of β-hCG prior to therapy is an important factor for predicting therapeutic outcomes. It should be noted that the success of the therapy decreases notably in case of high β-hCG level.